Mechanical performance of eco-efficient hollow clay bricks incorporating industrial nano-crystalline aluminium sludge - Cavaco, Eduardo S.; Grilo, Inês; Gouveia, João Paulo; Júlio, E.; Neves, Luís C. (Taylor & Francis, 2018)
In this paper, mechanical properties of a new structural and eco-efficient hollow clay bricks are investigated. The principal goal was to recycle residual sludge from aluminium anodizing industries by incorporating it in the raw material of bricks, thus contributing for the sustainability of the construction sector. It was also an objective to enhance thermal properties of the bricks, contributing to improve the energy efficiency of buildings, and maintain their mechanical properties.